Prototype scheme for differential protection of power transformer using ANN - Kumar N.; Gupta H.; Singh S.P. (My University, 2025)
The increased growth in power systems both in size and complexity has brought the need for fast and reliable protection scheme for major equipments like transformer. The implementation of a pattern recognizer for power system diagnosis can provide great advancement in the protection field. The work reported in this paper demonstrates the use of an Artificial Neural Network (ANN) as a pattern classifier for differential relay operation in the protection scheme for power transformer protection. This ANN-based scheme monitors different operating conditions of the transformer, detects the fault and issues the trip signal in the case of internal fault only. Tests were carried out using experimental set-up and through Results showing the performance of the protection scheme indicate that it is fast and reliable ©2008 IEEE.